The Influence of Compensation and Work Facilities on the Performance of Inpatient Nurses at Tk.II Iskandar Muda Hospital - Rengga Brata Arisa Yudha; Mochamad Vrans Romi (Fakultas Ekonomi dan Bisnis, Universitas Jenderal Achmad Yani, 2024)
The research found the Influence of compensation and work facilities on the performance of inpatient nurse at Tk.II Iskandar Muda Hospital Kesdam Iskandar Muda. The data used in this study is preliminary data that was collected using a survey strategy using an online questionnaire with responses from researchers who were paid in accordance with the study's objectives. The study's time horizon is cross-sectional, with a minimum of 122 respondents. This research uses the statistical hypothesis test with the version 22 of the Social Science Program (SPSS). This study reduces compensation and work facilities. The study's findings indicate that the aforementioned variable has a positive and significant impact on work performance. Workplace facilities indicate that the results of this study have a positive and significant impact on work environment. The results of this study indicate that compensation and work facilities have a positive and significant impact on the work force of domestic workers in a hospital.